Teoria da mente e desenvolvimento infantil: um procedimento de intervenção com crianças no interior da Bahia - Souza, Adriana Soares Freitas de (2009)
The ability of attributing mental states - desires, intentions and beliefs - to oneself and others has been named theory of mind. Such ability is necessary for the human being to understand and participate in social relations and it can be revealed in false-belief tasks. There are signals that the child s participation in conversational activities about events that involve mind actions may influence the ability of attributing beliefs to others. Thus, the existence of a narrow relation between the theory of mind and language can be accepted. The purpose of the present study was to check the effects of an intervention process in which mental states of beliefs are explained to participants through conversations in ludic situations concerning the ability of understanding the other ones mind. It was accepted the hypothesis that such process contributes to the acquisition of the ability of attributing mental states of beliefs in preschool children. The present research, which is quisi-experimental type, was developed in three steps: a) pre-test: a test of verbal level and the first five tasks in theory of mind from Wellman and Liu scale were performed; b) intervention: four ludic sessions were carried out in which the researcher told stories involving comprehension and attribution of mental states to the characters, i.e., desires, intentions and beliefs to others, based on the tasks from Wellman and Liu scale, by using some language that emphasizes mental verbs; post-test: in post-test 1, on the day after the last intervention, five pre-test tasks were performed; in post-test 2, two weeks later, the same pre-test tasks were performed. The participants were 10 children, 6 boys and 4 girls, whose age range was 4,9 - 5,11 years old; their socioeconomic level is low and they attend a city public school in the state of Bahia. The results showed that the children achieved progress in understanding false-belief after the intervention process. In general, the conversation strategies used in the intervention collaborated on the advancement in the capacity of attributing mental states of beliefs in others. These results support the hypothesis of a relation between the theory of mind and the development of language